On Wilfrido Ma. Guerrero’s Frustration: Denouncing Official Culture of traditional Asian Family - Herujiyanto, Antonius (Universitas Sanata Dharma, 2014)
The purpose of this study is twofold, looking into a Philippine dramatic text, Wilfrido Ma. Guerrero’s three-act play Frustration, and finding the meaning of the work. The aim of bringing to bear upon it the analytical perspectives of New Criticism, Russian Formalism and Structuralism, is to highlight the belief that any approach implemented is but to reveal its covert meaning. This is indirectly agreeing with the credo l’art pour l’art and that of the so-called instrumentalism [or rather, antirealism] instead of exercising the ‘weird’ attitude of investigating the political style of pretending to appreciate and be concerned with literary works. Keywords: criticism, colonialism, culture, covert meaning